Risk factors for posterior capsule rupture in cataract surgery as reflected in the European Registry of Quality Outcomes for Cataract and Refractive Surgery. Issue 1 (January 2022) - Segers, Maartje H.M.; Behndig, Anders; van den Biggelaar, Frank J.H.M.; Brocato, Lucia; Henry, Ype P.; Nuijts, Rudy M.M.A.; Rosen, Paul; Tassignon, Marie-José; Young, David; Stenevi, Ulf; Lundström, Mats; Dickman, Mor M.
Abstract : Important risk factors for posterior capsule rupture were identified based on the EUREQUO, such as increasing age, poor preoperative visual acuity, hyperopic target refraction, corneal opacities, diabetic retinopathy, and glaucoma. Abstract : Purpose: To analyze the incidence and risk factors for posterior capsule rupture (PCR) in cataract surgery. Setting: European clinics affiliated with the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO). Design: Retrospective cross-sectional register-based study. Methods: Data were obtained from the EUREQUO. The database contains data on demographics, comorbidities, and intraoperative complications, including PCR for the study period from January 1, 2008, to December 31, 2018. Univariate and multivariate logistic regression analyses were performed to estimate the (adjusted) odds ratio (OR) and 95% confidence intervals (CIs). Results: We analyzed EUREQUO registry data of 2, 853, 376 patients, and 31, 749 (1.1%) cataract surgeries were complicated by a PCR. Data were available of 2 853 376 patients, and 31 749 (1.1%) cataract surgeries were complicated by a PCR. The PCR rate ranged from 0.60% to 1.65% throughout the years, with a decreasing trend ( P < .001). The mean age of the PCR cohort was 74.8 ± 10.5 years, and 17 29 (55.5%) patients were female. Risk factors most significantly associated with PCR were corneal opacities (OR 3.21, 95% CI, 3.02-3.41, P < .001), diabetic retinopathy (OR 2.74, 95% CI, 2.59-2.90, P < .001), poor preoperative visual acuity (OR 1.98, 95% CI, 1.88-2.07, P < .001), and white cataract (OR 1.87, 95% CI, 1.72-2.03, P < .001). Conclusions: Risk factors for PCR were identified based on the EUREQUO, and the incidence of this complication is decreasing over time.